Protective role of female gender in programmed accelerated renal aging in the rat - Pijacka, Wioletta; Clifford, Bethan; Tilburgs, Chantal; Joles, Jaap A.; Langley-Evans, Simon C.; McMullen, Sarah (Wiley Open Access, 2015)
The aging kidney exhibits a progressive decline in glomerular ﬁltration rate, accompanied by inﬂammatory and oxidative damage. We hypothesized that accelerated, age-related progression of renal injury is ovarian hormones-dependant. To address this we used an established model of developmentally programmed accelerated renal aging in the rat, superimposed by ovariectomy to assess interactions between ovarian hormones and the aging process. Under our experimental conditions, we found that kidney function worsens with age, that is GFR reduces over 18 month analyzed time-course and this was worsened by fetal exposure to maternal low-protein diet and absence of estrogen. Reduction in GFR was followed by increases in albuminuria, proteinuria, inﬂammatory markers, and tissue carbonyls, all suggesting inﬂammatory response and oxidative stress. This was associated with changes in AGTR2 expression which was greater at 18 months of age compared to earlier time points, but in MLP offspring only. Our studies show an inﬂuence of ovarian hormones on programmed accelerated renal aging and the AGTR2 across the lifespan. The main ﬁndings are that ovariectomy is a risk factor for increased aging-related renal injury and that this and oxidative damage might be related to changes in AGTR2 expression.